Current Psychopathological Symptoms in Children and Adolescents Who Suffered Different Forms of Maltreatment - Paola De Rose; Fortunata Salvaguardia; Paola Bergonzini; Flavia Cirillo; Francesco Demaria; Maria Pia Casini; Deny Menghini; Stefano Vicari (The Scientific World Journal)
The aim of the present study is to evaluate the current psychopathological problems of different forms associated with maltreatment on children’s and adolescents’ mental health. Ninety-five females and ninety males with a mean age of 8.8 years who have suffered in the last six months different forms of abuse (physical, sexual, and emotional) and neglect were included in the study. The current reaction to trauma as directly observed by clinical instruments was examined. Differences in gender, age at the time of medical examination, familial psychiatric disorders, neuropsychiatric status, and type of maltreatment were also taken into account. Results documented that 95.1% of abused children and adolescents developed a psychiatric disorder or a subclinical form of a Posttraumatic Stress Disorder (PTSD). Moreover, our data demonstrate a role for gender, age, and familial psychiatric comorbidity in the current psychopathological problems associated with maltreatment. Overall, our findings can help clinicians make a diagnosis and provide efficient treatment and prevention strategies for child maltreatment and abuse.